Properties of convective oxygen and silicon burning shells in supernova progenitors. Issue 2 (25th September 2017) - Collins, Christine; Müller, Bernhard; Heger, Alexander
Abstract: Recent 3D simulations have suggested that convective seed perturbations from shell burning can play an important role in triggering neutrino-driven supernova explosions. Since isolated simulations cannot determine whether this perturbation-aided mechanism is of general relevance across the progenitor mass range, we here investigate the pertinent properties of convective oxygen and silicon burning shells in a broad range of pre-supernova stellar evolution models. We find that conditions for perturbation-aided explosions are most favourable in the extended oxygen shells of progenitors between about 16 and 26 solar masses, which exhibit large-scale convective overturn with high convective Mach numbers. Although the highest convective Mach numbers of up to 0.3 are reached in the oxygen shells of low-mass progenitors, convection is typically dominated by small-scale modes in these shells, which implies a more modest role of initial perturbations in the explosion mechanism. Convective silicon burning rarely provides the high Mach numbers and large-scale perturbations required for perturbation-aided explosions. We also find that about 40 per cent of progenitors between 16 and 26 solar masses exhibit simultaneous oxygen and neon burning in the same convection zone as a result of a shell merger shortly before collapse.